STUDENTS' PARTICIPATION IN ONLINE LEARNING DURING COVID-19 PANDEMIC IN EAST PRIANGAN - Yuyun Nuriyah Muslih; Imas Komalasari; Ai Hilyatul Halimah (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2021)
Abstract:Participation in learning is used as a means to create effective learning to achieve learning success. Likewise, with online learning, participation has an important position that students must have. The form of learning participation can be realized in visual, oral, listening, writing and mental activities. The purpose of the study was to determine the level of student participation in online learning during the Covid-19 pandemic. The research population was all students in East Priangan, and the sample selected was 85 students who live in East Priangan. The research method used was survey research with a quantitative approach and data collection techniques through distributing questionnaires to the sample consisting of 85 students and indirect interviews. The research results indicated that online learning during the Covid-19 pandemic could be an effective way to be implemented, although, in practice, there were still some technical and non-technical obstacles.Abstrak:Partisipasi dalam pembelajaran digunakan sebagai sarana untuk menciptakan pembelajaran yang efektif guna mencapai keberhasilan belajar. Begitupun dengan pembelajaran online, partisipasi memiliki posisi penting yang harus dimiliki mahasiswa. Bentuk partisipasi belajar dapat diwujudkan dalam aktivitas visual, oral, menyimak, menulis dan mental. Tujuan penelitian adalah untuk mengetahui tingkat partisipasi mahasiswa dalam perkuliahan online di masa pandemi Covid-19. Populasi penelitiannya adalah seluruh mahasiswa yang ada di Priangan Timur, dengan sampel yang digunakan yaitu 85 mahasiswa yang berdomisili di Priangan Timur. Adapun metode penelitiannya menggunakan penelitian survei dengan pendekatan kuantitatif dan teknik pengumpulan datanya melalui penyebaran kuisioner kepada sample yang terdiri dari 85 mahasiswa dan wawancara tidak langsung. Hasil penelitian menunjukan bahwa perkuliahan online di masa pademi Covid-19 dapat dikatakan sebagai cara yang efektif untuk dilaksanakan, meskipun dalam pelaksanaannya masih ditemui adanya beberapa kendala baik teknis maupun non teknis.